Evolution of the Double‐ITCZ Bias Through CESM2 Development. (1st July 2019) - Woelfle, M. D.; Bretherton, C. S.; Hannay, C.; Neale, R.
Abstract: The structure of the east Pacific Intertropical Convergence Zone (ITCZ) as simulated in the Community Earth System Model version 2 (CESM2) is greatly improved as compared to its previous version, CESM version 1. Examination of intermediate model versions created as part of the development process for CESM2 shows the improvement in the ITCZ is well correlated with a reduction in the relative warmth of southeast Pacific sea surface temperatures (SSTs) as compared to the broader tropical mean. Cooling SST in this region enhances the zonal SST and surface pressure gradients and reduces the anomalously southward SST gradient present in boreal spring in early version of CESM2. The improvements in southeast Pacific SST are attributed to increases in low cloud cover and the associated shortwave cloud forcing over the southeast. Sensitivity tests using fixed SST simulations demonstrate the increase in cloud cover between two intermediate model versions, 119 and 125, to be driven by removal of the dependence of autoconversion and accretion rates on cloud water variance as well as the removal of a secondary condensation scheme. Both of these changes reduce drizzle rates in warm clouds increasing cloud lifetime and cloud fraction in the stratocumulus to trade cumulus transition region. The improvements in southeast Pacific shortwave cloud forcing and ITCZ climatology persist through subsequent changes to the cloud microphysics parameterizations. Despite improvements in the east Pacific ITCZ, the global mean ITCZ position and Pacific cold tongue bias strength do not exhibit a systematic improvement across the development simulations. Key Points: Increased southeast Pacific cloud fraction and improved SST gradients alleviate the double‐ITCZ bias in CESM2 Increased cloud fraction is driven by retuning of liquid cloud microphysics not the implementation of CLUBB boundary layer scheme Despite improvements in east Pacific precipitation, the global mean ITCZ position and cold tongue biases show no consistent change